2015
DOI: 10.5937/aaser1539051v
|View full text |Cite
|
Sign up to set email alerts
|

Effect of mineral and organic fertilization of alfalfa on some seed yield characteristics, root biomass accumulation and soil humus content

Abstract: Abstract:A field trial at the Institute of Forage Crops, Pleven, Bulgaria (2000-2003 was conducted to study the effect of mineral and organic fertilization on seed yield of alfalfa, root biomass accumulation and soil humus content. Alfalfa variety 'Victoria' was grown on a leached chernozem soil without irrigation. Rates of 70, 140 and 210 kg ha -1 mineral nitrogen (active ingredient) were tested as ammonium nitrate and well-matured cattle manure. It was found that mineral and manure fertilization at 140 and 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…The biochemically active nature of humic acid works to enhance formation of root mass as well. Soil humus was found to be humic type of humus for both areas of alfalfa grown for forage and seeds (Vasileva and Kostov 2015b). The leached chernozem soil subtype (Haplic) without irrigation over five consecutive years.…”
Section: Resultsmentioning
confidence: 97%
“…The biochemically active nature of humic acid works to enhance formation of root mass as well. Soil humus was found to be humic type of humus for both areas of alfalfa grown for forage and seeds (Vasileva and Kostov 2015b). The leached chernozem soil subtype (Haplic) without irrigation over five consecutive years.…”
Section: Resultsmentioning
confidence: 97%
“…The mineral nitrogen concentrations quantified in our study failed to explain the observed differences in nitrogen fixation, as nitrate concentrations did not decrease in accordance with the observed increase in Ndfa. With available nitrogen levels in our samples being high enough to meet plant nitrogen demands (Vasileva and Kostov, 2015), it seems unlikely that changes in soil nitrogen cycling were responsible for the increased Ndfa. However, past studies indicate that the impact of antibiotics on soil processes typically declines with time (Cui et al, 2014; Chessa et al, 2016).…”
Section: Discussionmentioning
confidence: 97%
“…Field trials supposed to enable selection of the most successful genotypes which is critical because of the existence of Genotype by Environment interaction . To assess this interaction we are forced to conduct field trials in several environments and/or years (Vasileva, Kostov, 2015;Babić et al ., 2019;Ugrenović et al ., 2019;Mandić et al ., 2020) .…”
Section: Alfalfa Yieldmentioning
confidence: 99%